2020
DOI: 10.3389/fnagi.2020.00113
|View full text |Cite
|
Sign up to set email alerts
|

Aging Reduces Estradiol Protection Against Neural but Not Metabolic Effects of Obesity in Female 3xTg-AD Mice

Abstract: Vulnerability to Alzheimer's disease (AD) is increased by several risk factors, including midlife obesity, female sex, and the depletion of estrogens in women as a consequence of menopause. Conversely, estrogen-based hormone therapies have been linked with protection from age-related increases in adiposity and dementia risk, although treatment efficacy appears to be affected by the age of initiation. Potential interactions between obesity, AD, aging, and estrogen treatment are likely to have significant impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Generally, estrogen can protect the brain through its vasodilatory, anti-apoptotic, antioxidant, and anti-inflammatory actions [ 15 , 64 ]. Rodent studies have also shown protective effects of estrogen against Aβ [ 59 , 65 , 66 ]. A limitation of our work is that menopause is not taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, estrogen can protect the brain through its vasodilatory, anti-apoptotic, antioxidant, and anti-inflammatory actions [ 15 , 64 ]. Rodent studies have also shown protective effects of estrogen against Aβ [ 59 , 65 , 66 ]. A limitation of our work is that menopause is not taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reduced E2 levels during the menopause transition have been linked to increased risk of type 2 diabetes [ 36 ]. In this study, levels of E2 impacted bacteria carbohydrate metabolic pathways, which may account for the protective metabolic effects of E2 which wane during aging [ 10 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that imbalances in various neuroendocrine related systems, such as the HPA axis, HPG axis, insulin and brain-gut axis, can be observed in people with early stage AD, while related hormone therapy has been proved to achieve better results only in the early stages of aging ( 84 , 85 ). This suggests that the intervention of AD through the neuroendocrine related axis needs to be carried out before the irreversible accumulation of neurotoxic substances, and there is still a large gap in the relevant early drug treatment in western medicine intervention.…”
Section: Manuscript Formattingmentioning
confidence: 99%